POLA PENGASUHAN KESEHATAN REPRODUKSI ORANG TUA DI KOTA MOJOKERTO - Dhonna Anggreni (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2017)
The success of parents in inculcating reproductive health behaviors in children, depends largely on the model and type of parenting patterns applied by parents. But reproductive health education for children is still considered taboo by the community. This research is cross-sectional research. This study identifies parenting patterns of reproductive health of parents in Mojokerto City. The population of this study were all students and 4th and 5th grade students of SDN Meri 1 and SDN Kranggan 2 Kota Mojokerto with their parents of 140 people. The sampling technique is simple random sampling, and the total sample is 103 people. The results showed that as much as 37.9% of parents apply a democratic parenting pattern in providing reproductive health education to their children